Stereotactic ablative body radiotherapy of ventricular tachycardia. Single italian centre experience. (19th May 2022) - Marinelli, A; Giaj Levra, N; Trachanas, K; Costa, A; Sicignano, G; Cuccia, F; Corso, M; Alongi, F; Molon, G
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Ventricular tachycardia (VT) is a life-threatening condition. Usual management of VT is based on anti-arrhythmic drugs or catheter ablation. In this scenario, stereotactic body radiation therapy (SBRT) is arising as an attractive non-invasive alternative for the treatment of VT in some patients (pts). Purpose: The aim of this study was to assess safety, feasibility and outcomes of SBRT in fragile pts admitted in our centre for VT storms. Methods: Pts with implantable cardioverter-defibrillator (ICD), presenting with VT storms and not responsive to drugs or suitable for catheter ablation were enrolled for SBRT. All pts underwent a computed tomography (CT) and an 18F-fluorodeoxyglucose positron emission (FDG PET)-CT scan in order to detect a possible area of scar responsible of the VT. All pts had also an electrophysiological study and ventricular programmed stimulation inducing clinical VT while wearing a multi-electrodes ECG vest. Merging the CT scan imagines and the VT 3D reconstruction, we identified the possible circuit of the VT and its exit sites. Treatment planning was performed for a total dose of 21-25 Gy delivered in a single session. For the first year, follow-up (FU) were scheduled every 3 months since the SBRT treatment. Toxicity was prospectively assessed. Results: From January 2020 to March 2021, we treated 6 (5 males) pts. Mean age was 78±4. NYHA class was II for 3 pts, 2 were class III and only one pts was class IV. Four pts had an ischaemic heart disease background, two had dilated cardiomyopathy (DCM). Mean ejection fraction (EF) was 31±6%. The mean FU was 17 months, with the longest of 23 months. Of these 6 pts, only one died because of end stage heart failure, no VT/VF were recorded on his ICD. This was the pts with DCM and class NYHA IV at the time of procedure. Of the 5 pts remaining, 2/5 reported new therapies delivered by their ICDs. One pts had a single ICD shock during acute urine tract infection and sepsis at one month since SBRT. ICD interrogation documented inappropriate shock on fast conducted atrial fibrillation. No VTs have been recorded after 7 months. The other pts was admitted after 5 months since SBRT. The ICD showed appropriate therapies on VTs. This pts had the biggest scar volume compared to the others (anterior wall of the left ventricle with aneurysmatic apex). On the other 3 pts, no VTs were recorded by ICDs. Of these 3 pts, interestingly, 2 had class NYHA III and the mean EF 28.6±3%. The overall outcome with no appropriate ICD shocks due to VTs is above 70%. No radiotherapy toxicity was documented. Conclusion: To the best of our knowledge this is one of the biggest groups of pts treated with this technology and the longest FU so far, of a single centre in Italy. SBRT seems to be a safe and feasible approach to treat fragile pts with VTs when not suitable for standard catheter ablation or responsive to medications. It also shows a good outcome even in pts with more advanced heart failure.